A fixed movable resin-bonded fixed dental prosthesis – A 16 years clinical report. Issue 1 (January 2016) - Botelho, Michael G.; Lam, Walter Y.H.
Abstract: Patients: This report describes the case of a 48-year-old female patient who initially received a 4-unit fixed-fixed (FF) resin-bonded fixed dental prosthesis (RBFDP) for replacement of mandibular left second premolar and first molar. Twenty-one months later, debond of the RBFDP was found at one of retainers. A new fixed-movable RBFDPs with a modified non-rigid connector as well as increased resistance form features was placed and successfully retained at the 16-year clinical review. Discussion: RBFDPs are a conservative tooth replacement option that requires minimum tooth preparation and retention by a resin cement to etched enamel. However debonding is the most frequently seen complication and has been attributed to the relative movement between abutment teeth during function that stress the bonding interface. This case report highlights the use of modified non-rigid connector which allows relative movement between abutment teeth and therefore a reduced stress on the bonding interface. Conclusion: It is proposed that the use of modified non-rigid connectors that allow independent movement between the abutment teeth during function was responsible for the long term clinical success of fixed-movable RBFDPs.